COVID-19 symptoms and antibody formation in competitive cross-country skiers - Laatkainen-Raussi, V. (2022)
The COVID-19 pandemic set the whole world in front of a relatively new situation. Knowledge of the new infection, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV 2), was sparse and people in every industry started to rethink their habits and guidelines. Acute respiratory illnesses and infections are a major burden to competitive athletes and some guide lines considering avoiding infections and return to sport already exist. However, proper scien tific based guidelines were and are still missing, especially considering return to sport. The purpose of this thesis was to enhance the understanding of respiratory viral infections in athletes and to describe the nature COVID-19 in a cohort of Finnish cross-country skiers.